Phytochemical Screening, In-vitro Cytotoxic and Antimicrobial Activity of Methanolic Extract of Leaves of Ficus sagittata vahl. - Zaman, Rashaduz (Innovare Journal of Life Sciences, 2016)
Objective: The present study was aimed to evaluate the brine shrimp cytotoxic lethality and antimicrobial activity of methanolic extract of leaves of Ficus sagittata vahl.. Phytochemical screening was also evaluated. Methods: To determine these activities, Ficus sagittata vahl. was tested against various gram positive and gram negative bacterial organism through disc diffusion method and cytotoxic activity by brine shrimp lethality assay. For antimicrobial activity, various concentrations of 1000 µg/disc, 800 µg/disc, 500 µg/disc, and 300 µg/disc were used. For cytotoxic activity various concentration of 5 µg/ml, 10 µg/ml, 50 µg/ml, 100 µg/ml, 150 µg/ml, and 200 µg/ml were used. Results: The methanolic extract showed remarkable antimicrobial activity against all the organism but is showed the highest activity against Escherichia coli and its zone of inhibition was 23 mm at concentration of 1000 µg/disc compared to 33 mm that of positive control kanamycin. The crude methanolic extract showed strong cytotoxic activity with LC50 value of 31.73 µg/ml compared to that of 0.839 µg/ml exhibited by the positive standard vincristine sulphate. The phytochemical screening revealed the presence of phenols, tannins, flavonoids, alkaloids, carbohydrate, saponin, glycosides, and steroids. Conclusion: From our evaluation, we conclude that, Ficus sagittata vahl. possesses the potentiality for further research as an antimicrobial and cytotoxic agent.